It''s all in for the HER family in tumorigenesis. (January 2010) - Lee IV, Major Kenneth; Sharma, Anupama; Czerniecki, Brian J
Evaluation of: Prickett TD, Agrawal NS, Wei X et al. Analysis of the tyrosine kinome in melanoma reveals recurrent mutations in ERBB4. Nat. Genet. 41(10), 1127––1132 (2009)[1] . The EGF receptor family is a group of receptor tyrosine kinases that have been implicated in the development of a variety of malignancies. As such, they have been targeted in the generation of pharmacologic agents, several of which have been approved as anti-tumor therapeutics. The lone exception is ERBB4, for which the function and relationship to cancer are not yet clear and no targeted therapies exist. The paper under evaluation demonstrates a role for ERBB4 mutations in the development of melanoma. It identifies ERBB4 mutations present in melanomas that augment proliferation and cell survival and thus contribute to dysregulated growth. Furthermore, it shows that agents targeting the EGF receptor family can reduce the proliferation of melanoma cells harboring these mutations. These findings further emphasize the role of the ERBB subfamily in tumorigenesis and establish ERBB4 as a new target in the development of anti-tumor strategies.